THE EFFECT OF SHARIA GOVERNANCE ON THE REPUTATION OF INDONESIAN SHARIA BANK: PENGARUH SYARIAH GOVERNANCE TERHADAP REPUTASI BANK SYARIAH INDONESIA - Amri Nasution, Khoirul (UPMI Proceeding Series, 2023)
Islamic banking is currently growing rapidly and has become a part of financial life in the Islamic world. However, there are two realities that are important to observe in the life of Islamic banking in Indonesia. First, Islamic banks have not achieved a market share of 5 percent. Second, there is a decrease in adherence to Islamic teachings towards sharia principles. Therefore it is necessary to develop a strategy through the implementation of sharia governance. The implementation of Sharia Governance is expected to have an impact on the reputation and trust of customers which in turn can increase the market share of Islamic banks. Based on this background, the research problem is how to implement sharia governance and its impact on reputation and trust in sharia banks. The analysis technique used is descriptive. The results of this data calculation show that the implementation of sharia governance includes six indicators, namely transparency, accountability, responsibility, independence, fairness, and sharia compliance which have shown good results. Sharia compliance is a dominant indicator of Islamic governance, while accountability and fairness are weak indicators of implementing sharia governance and have a significant effect on reputation and customer trust in sharia banking.